2019
DOI: 10.1177/1535370219843830
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of exercise training on diabetic kidney disease in ovariectomized rats with type 1 diabetes

Abstract: This study evaluated the effects of moderate regular physical exercise on lipid peroxidation, inflammation and renal function and structure in streptozotocin (STZ)-induced ovariectomized diabetic rats. Twenty-four Wistar rats were anesthetized and submitted to bilateral ovariectomy. The rats were divided into four experimental groups: ovariectomized control (OC), ovariectomized trained control (OTC), ovariectomized diabetic (OD), ovariectomized trained diabetic (OTD). The OTD and OTC groups were submitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
18
0
3
Order By: Relevance
“…81 Studies have shown that low to moderate intensity aerobic exercise seems to exert renoprotective effects in patients with T1DM and T2DM 18,8284 and in experimental models of DM. 7,8,85,86 Moderate aerobic exercise improved the insulin sensitivity, glucose uptake 83,87–89 lipid levels, endothelial function, pancreatic beta cell function, and decreased insulin resistance 70,90 , tubular injury, and microalbuminuria in patients with T2DM. 18 Additionally, a recent study has shown that a calorie-restricted diet associated with this type of exercise reduced inflammation and oxidative stress delayed the development of renal failure by postponing renal fibrosis in patients with T2DM in stage 3 DKD.…”
Section: Effects Of Low To Moderate Aerobic Exercise Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…81 Studies have shown that low to moderate intensity aerobic exercise seems to exert renoprotective effects in patients with T1DM and T2DM 18,8284 and in experimental models of DM. 7,8,85,86 Moderate aerobic exercise improved the insulin sensitivity, glucose uptake 83,87–89 lipid levels, endothelial function, pancreatic beta cell function, and decreased insulin resistance 70,90 , tubular injury, and microalbuminuria in patients with T2DM. 18 Additionally, a recent study has shown that a calorie-restricted diet associated with this type of exercise reduced inflammation and oxidative stress delayed the development of renal failure by postponing renal fibrosis in patients with T2DM in stage 3 DKD.…”
Section: Effects Of Low To Moderate Aerobic Exercise Trainingmentioning
confidence: 99%
“…30 Evidence suggests that increased expression of ECM proteins in the diabetic kidney is mainly mediated by profibrogenic cytokine TGF-β1. The progressive accumulation of ECM is a critical factor in the progression of DKD, present in both humans 31,32 and experimental animals, 7,8 and contributes to the development of glomerulosclerosis and tubulointerstitial fibrosis. 33,34 Under normal conditions, the main mesangial ECM proteins are fibronectin, laminin, type IV collagen (α1 and α2 chains), and proteoglycans.…”
Section: Hemodynamic Disordersmentioning
confidence: 99%
See 3 more Smart Citations